The impact of match location and crowd attendance during COVID-19 on technical performance in elite Gaelic football - Boyle, E.; Mangan, S.; McDermott, L. (Sport Performance & Science Reports, 2021)
Despite the popularity and perceived importance of technical analysis within Gaelic games, there is a distinct lack of published research in terms of team performance indicators in Gaelic football. Elite Gaelic football literature has reported teams to take 27 ± 5 shots per game, with teams committing 21 ± 5 fouls per game [23]. Further research is required to determine if these findings are normative for Gaelic football, and if variations exist when playing location and crowd is considered. In line with sports such as Australian football [8], soccer [34], rugby, basketball and handball [35], home advantage has been previously established in Gaelic football [21]. Elite Gaelic football research has observed home advantage in the championship qualifiers to be more prevalent from 2010-2015 than the previous 10 seasons (2001-2010). This investigation also showed that home advantage was evident overall with home teams winning on 56.1 ± 4.1 % of occasions in contrast to away teams winning on 37.5 ± 2.5 % of games [21]. Although the concept of home advantage is well established in team sports, the impact of match location on technical performance indicators in Gaelic football requires further investigation. Due to the COVID-19 pandemic, supporters have been prevented from attending sporting events and lending their teams live support, including Gaelic football. Elite soccer research identified a relationship between crowd size and home advantage [15], while other elite adult and elite youth soccer literature discovered home advantage was evident even when attendances were minimal [33], or even zero [34]. Recent findings suggest that even if the home crowd matters, there is no straightforward relationship between crowd size and home advantage, with no significance discovered between the two variables [19]. Research investigating home advantage and referee bias in elite soccer discovered a significantly greater magnitude of referee bias to the home team with increased crowd density [16]. Similarly, elite soccer research examining match-play over ten seasons discovered home team bias significantly increased with increasing crowd size [4]. Regarding location and crowd, elite soccer research investigating the effect of crowd support on referee decision-making discovered a positive correlation between home team bias and crowd density [11]. However, the findings of other elite soccer literature examining points per game suggests that home advantage exists for teams playing in their own stadiums, regardless of whether a crowd is present [34]. This suggests that crowd support is not a necessary precondition for the home advantage. With respect to these presumably only temporary conditions, a gap in literature exists regarding the impact of crowd attendance on technical performance in Gaelic football.